Laboratory Study on Comparison of the Scour Depth and Scour Length of Groundsill with the Opening and Groundsill without the Opening - Ani Hairani; Djoko Legono (Journal of the Civil Engineering Forum, 2016)
River bed control structure what so called groundsill or bottom sill is built for controlling a river bed to remain stable against degradation. Unlike other river obstacles, the presence of groundsill might cause sediment retention upstream of the structure; hence it reduces the supply of sediment to the downstream part of the river. At some extent, the above situation might create unexpected negative impact, not only cease the sediment migration but also disable fish migration, as well as the utilization of river for navigation. This paper presents the hydraulic investigation on various models of groundsill, i.e. groundsill without the opening and groundsill with a certain type of the opening. Series of laboratory experiments were conducted on an open channel flow of 0.75m width and longitudinal slope of 0.05%. There were two types of groundsill, i.e. groundsill without the opening with 0.75m width and 0.05m height, and groundsill with the opening of 0.39m width and 0.005m height of crest at the opening and 0.05m at the wings. Various flow rates were then introduced, necessary data were taken, and the hydraulic phenomena were studied. The results showed that groundsill without the opening produced non-dimensional (relative to the channel width) scour depth of 0.036, and scour length of 0.253. Groundsill with the opening produced scour depth of 0.013 and 0.024 near the downstream end of the wing section and the opening respectively. The scour length of the groundsill with the opening is 0.080 and 0.293 near the downstream end of the wing section and the opening section respectively. Moreover, it can be noted that the presence of the scour depth and scour length of the groundsill with the opening was generally much smaller rather than that of groundsill without the opening. The above results give the evidence that groundsill with the opening is much friendlier and also more suitable for the environment needs.Keywords: control structure, environmentally sound, groundsill, hydraulic phenomenon